#118 : The “HERAQoL-P”: Development of a Meaningful, International Quality of Life Tool for PCOS - Jodie Avery; Stephanie Pirotta; Geranne Jiskoot; Melanie Gibson Helm (Fertility & Reproduction, 2023)
Background and Aims: Women with Polycystic Ovary Syndrome (PCOS) have diverse experiences of Quality of Life (QoL) depending on their age, ethnicity, socio economic status, severity and phenotype. PCOS, a common endocrine condition in women, exhibits problematic symptoms related to fertility, weight gain, mental health and sleep. QoL is an important health outcome, yet standard measures include predefined items, that may be unimportant to individuals. The full physical, emotional, and social impact of PCOS is not captured with existing PCOS QoL measures. These factors need to be addressed within person-centred care in order to achieve the best possible health outcomes in both the short and long term. We aim to scope and understand priorities for quality of life (QoL) dimensions from women with PCOS throughout life, to provide a conceptual framework for the creation of a meaningful, scientifically validated quality of life tool. Method: Based on the Schedule for the Evaluation of Individual Quality of Life (SEIQoL) questionnaire, we surveyed 80 women and interviewed 17 women diagnosed with PCOS in Australia, with another 93 completing the survey in the Netherlands, about aspects of life important for their quality of life. Interview questions include the impact of this condition on physical, mental and emotional health, and understand whether PCOS affects women differently according to their symptoms and background profile. Results: This work informs the development of a new QoL tool which will be internationally validated, reflecting the diverse PCOS features with the greatest impact, enabling better evaluation of Patient Reported Outcomes. Conclusion: A high-quality QoL questionnaire could highlight women’s specific priorities, and then measure whether their healthcare addresses such priorities. We will then create the HERAQoL-P, with extensive potential to have impact, in both research and clinical care, adding to the evidence base for PCOS.